mTORC2 controls cancer cell survival by modulating gluconeogenesis - Khan, MW (Cell Death Discov, 2015)
For rapid tumor growth, cancer cells often reprogram the cellular metabolic processes to obtain enhanced anabolic precursors and energy. The molecular changes of such metabolic rewiring are far from established. Here we explored the role of mTOR (mechanistic target of rapamycin), which serves as a key regulator of cell growth, proliferation and survival, in the metabolic reprograming of cancer cells. When we inhibited mTOR in human hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC) cells, using pharmacologic inhibitors or by RNA interference, we noticed shuttle of the glycolytic flux to gluconeogenesis pathway along with reduction in cellular proliferation and survival. Augmentation of gluconeogenesis was mechanistically linked to upregulation of the key gluconeogenic enzymes PCK1 and G6PC expressions, enhanced lactate dehydrogenase activity and glucose-derived lipogenesis without causing any attenuation in mitochondrial function. Interestingly, concomitant knocking down of PCK1 and not G6PC along with mTOR pathway could overcome the inhibition of cancer cell proliferation and survival. These observations were validated by identifying distinctive diminution of PCK1 and G6PC expressions in human HCC and RCC transcriptome data. Significant correlation between mTOR-dependent upregulation of PCK1 and cell death in different cancer cell lines further emphasizes the physiological relevance of this pathway. We reveal for the first time that inhibition of mTORC2 and consequent redistribution of glycolytic flux can have a prosurvival role in HCC and RCC cancer cells only in the presence of downregulation of gluconeogenesis pathway genes, thus identifying novel pivots of cancer cell metabolic rewiring and targets for therapy.